(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2010)
Metal-Oxide-Semiconductor Field-Effect Transistors (MOSFETs) offer many advantages due to their low noise and high associated gain at microwave frequencies. Therefore, they are well suited to the amplifier requirements of broadband light-wave receivers, through providing a high dynamic range and wide bandwidths. In this work, the performance of integrated optical receiver consisting of PIN-photodiode and MOSFET-based transimpedence type amplifier is analyzed. The effect of various device parameters on receiver performance is investigated in details. The simulation results show that the sensitivity (Psen) of an optical receiver is approximately constant if it is based on well-designed MOSFET.